Ecoenzym dan Pupuk Organik sebagai Pemanfaatan Sampah Organik Agribisnis - Sabrinatus Amalia Gustannanda; Umi Hafilda Al-Hanniya; Aulia Ulfah Farahdiba; Yayok Suryo Purnomo (Yayasan Literasi Sains Indonesia, 2022)
Puspa Lebo is sheltered by the Technical Implementation Unit for the Development of Agribusiness for Food Crops and Horticulture (UPT. PATPH) in East Java, which is engaged in agriculture and plantations which have not yet stepped forward in processing the waste produced. Harvest nursery activities are in the form of waste production, nagging, stems, fruit or vegetables that do not qualify for quality and post-harvest waste and are only carried out until incomplete combustion. The processing carried out can produce direct or indirect negative impacts on the environment such as air pollution, air pollution, and disruption of life in the environment. The largest organic waste produced from the cultivation of melon plants which has a volume of 4,860 kg/harvest for the last 3 months and coconut shell waste from the business activities of the surrounding community is 100 shells/day. Based on this, it is necessary to process organic waste and use it as an ecoenzyme and organic fertilizer, which has more value for UPT. PATPH. There are factors that affect plant growth, namely sunlight, humidity, temperature, incoming air, soil pH. Coconut shell organic waste has the potential to be used as a planting medium for cocopeat and coconut charcoal that can be used for personal use or as a result of Puspa Lebo partners. The manufacture and application of liquid organic fertilizers and ecoenzymes are considered effective on liquid organic fertilizers made from noni and guava fruit.